The mediating role of creative behavior in the relationship between transformational leadership and turnover intention - Tamaradieyefagha Edonomokumor; Richard Arhinful; Leviticus Mensah; Hayford Asare Obeng (Future Business Journal)
Abstract The study used the job characteristics model to investigate the mediating role of creative behavior in the relationship between transformational leadership and turnover intentions within the Nigerian oil and gas industry. Nigeria was chosen as the study’s country due to its status as a central hub for the oil and gas industry in West Africa. The industry faces high employee turnover rates, which result in higher recruitment expenses, loss of institutional knowledge, and disruptions in workflow. The study selected 17 oil and gas companies operating in Lagos State using cluster sampling. Within these clusters, data were collected from 356 employees through convenience sampling by administering print-based questionnaires. Covariance-based structure equation modeling (CB-SEM) and confirmatory factor analysis (CFA) were the methods used to analyze the data with the help of AMOS software. The study discovered that transformational leadership had a positive and significant influence on turnover intention and creative behavior. Creative behavior was discovered to have a positive and significant impact on turnover intention. The study found that creative behavior partially mediates the relationship between transformational leadership and turnover intention. Oil and gas companies should adopt transformational leadership practices to reduce employee turnover and foster a culture that encourages creativity, innovation, and sustained organizational performance.